2007
DOI: 10.1183/09031936.00106306
|View full text |Cite
|
Sign up to set email alerts
|

Histamine and tryptase modulate asthmatic airway smooth muscle GM-CSF and RANTES release

Abstract: Degranulating mast cells are increased in the airway smooth muscle (ASM) of asthmatics, where they may influence ASM function. The aim of the present study was to determine whether histamine and tryptase modulate ASM cell granulocyte-macrophage colonystimulating factor (GM-CSF) and RANTES (regulated on activation, normal T-cell expressed and secreted) release and also to examine which receptors are involved in this release.Confluent, quiescent ASM cells from asthmatic and nonasthmatic donors were treated with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
28
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(30 citation statements)
references
References 38 publications
1
28
0
Order By: Relevance
“…The asthmatic state has long been recognized as one that includes dysregulation of airway GPCRs, including those that act to contract and relax airway smooth muscle. Such alterations have been observed in vivo and ex vivo in human and animal airways and in cultured HASM cells (14)(15)(16)(17)(18)(19)(20). These findings include altered [Ca 21 ] signaling from G q -coupled receptors, such as M 3 -muscarinic and H1-histamine, and cAMP signaling from b 2 AR (14,17,18).…”
Section: Clinical Relevancementioning
confidence: 83%
See 1 more Smart Citation
“…The asthmatic state has long been recognized as one that includes dysregulation of airway GPCRs, including those that act to contract and relax airway smooth muscle. Such alterations have been observed in vivo and ex vivo in human and animal airways and in cultured HASM cells (14)(15)(16)(17)(18)(19)(20). These findings include altered [Ca 21 ] signaling from G q -coupled receptors, such as M 3 -muscarinic and H1-histamine, and cAMP signaling from b 2 AR (14,17,18).…”
Section: Clinical Relevancementioning
confidence: 83%
“…Even in passaged cultured HASM cells, without the addition of proinflammatory agents in the media, cells derived from patients with fatal asthma show distinct phenotypes compared with cells derived from donors without asthma. These include differences in receptor signaling, second messenger-dependent enzyme function, the response to viral infection, cell proliferation, and intracellular events, notably "distal" to early interaction genes (15,16,32). The breadth of documented changes in HASM phenotype from asthma or an inflammatory environment requires that potentially new therapeutic agents be tested in this context.…”
Section: Discussionmentioning
confidence: 99%
“…Pharmacological blockade suggested that the effects of histamine were predominantly mediated via the H1 and not the H2 receptor. This was unexpected as CHHABRA et al [47] predicted that stimulation of H2 receptors would increase intracellular cyclic adenosine monophosphate and thus inhibit GM-CSF release, while at the same time potentiating RANTES release. The authors therefore proposed that the H1-mediated effects predominated and occur via activation of H1-coupled phospholipase C. However, it must be borne in mind that G-protein coupled receptors (GPCRs), such as H1 and H2, that were once thought to mediate all their effects via modulation of intracellular cyclic nucleotides are now known to couple to many diverse signalling pathways [48].…”
mentioning
confidence: 90%
“…In the present issue of the European Respiratory Journal, CHHABRA et al [47] have examined the ability of two mast cell mediators, histamine and tryptase, to modify the synthetic ability of the ASM derived from both asthmatic and nonasthmatic subjects [47]. Specifically, they examined the release of the cytokine granulocyte-macrophage colony-stimulating factor (GM-CSF) and the RANTES (regulated on activation, normal T-cell expressed and secreted) chemokine.…”
mentioning
confidence: 99%
“…Therefore, mast cells participate in the development of allergic reactions through cross-linking of their surface high affinity receptors for IgE (FceRI) leading to degranulation and the release of vasoactive, proinflammatory compounds, such as metabolites, histamine, cytokines, proteolytic enzymes and arachidonic acid compounds. Human mast cell proteases increase C-C chemokine (CCL8) and fibronectin in cultured airway smooth muscle cells (41 ).…”
Section: Asthmamentioning
confidence: 99%